Handbook of troubleshooting plastics processes : a practical guide - Wagner, John R. (Wiley ; Scrivener, 2012)
"This handbook provides a framework for understanding how to characterize plastic manufacturing processes for use in troubleshooting problems. The technical level is for process engineers and production personnel"--Rersumé vydavatele
Keywords: zpracování plastů; tváření plastů; vstřikování plastů; řešení problémů; plastics processing; plastic moulding; injection moulding; problem solving; příručky; případové studie; elektronické knihy; handbooks, manuals, etc; case studies; electronic books